Deleterious Effects of Chronic Folate Deficiency in the Ts65Dn Mouse Model of Down Syndrome - Helm, Susan; Blayney, Morgan; Whited, Taylor; Noroozi, Mahjabin; Lin, Sen; Kern, Semira; Green, David; Salehi, Ahmad (Frontiers in Cellular Neuroscience, 2017)
Folate is an important B vitamin naturally found in the human diet and plays a critical role in methylation of nucleic acids. Indeed, abnormalities in this major epigenetic mechanism play a pivotal role in the pathogenesis of cognitive deficit and intellectual disability in humans. The most common cause of cognitive dysfunction in children is Down syndrome (DS). Since folate deficiency is very common among the pediatric population, we questioned whether chronic folate deficiency (CFD) exacerbates cognitive dysfunction in a mouse model of DS. To test this, adult Ts65Dn mice and their disomic littermates were chronically fed a diet free of folic acid while preventing endogenous production of folate in the digestive tract for a period of 8 weeks. Our results show that the Ts65Dn mouse model of DS was significantly more vulnerable to CFD in terms of plasma homocysteine and N5-methyltetrahydrofolate (5-MTHF) levels. Importantly, these changes were linked to degenerative alterations in hippocampal dendritic morphology and impaired nest building behavior in Ts65Dn mice. Based on our results, a rigorous examination of folate intake and its metabolism in individuals with DS is warranted.